Crocodile choline from Crocodylus siamensis induces apoptosis of human gastric cancer. Issue 3 (March 2017) - Mao, Xiao-Mei; Fu, Qi-Rui; Li, Hua-Liang; Zheng, Ya-Hui; Chen, Shu-Ming; Hu, Xin-Yi; Chen, Qing-Xi; Chen, Qiong-Hua
Crocodile choline, an active compound isolated from Crocodylus siamensis, was found to exert potent anti-cancer activities against human gastric cancer cells in vitro and in vivo. Our study revealed that crocodile choline led to cell cycle arrest at the G2/M phase through attenuating the expressions of cyclins, Cyclin B1, and CDK-1. Furthermore, crocodile choline accelerated apoptosis through the mitochondrial apoptotic pathway with the decrease in mitochondrial membrane potential, the increase in reactive oxygen species production and Bax/Bcl-2 ratio, and the activation of caspase-3 along with the release of cytochrome c. In addition, this study, for the first time, shows that Notch pathway is remarkably deregulated by crocodile choline. The combination of crocodile choline and Notch1 short interfering RNA led to dramatically increased cytotoxicity than observed with either agent alone. Notch1 short interfering RNA sensitized and potentiated the capability of crocodile choline to suppress the cell progression and invasion of gastric cancer. Taken together, these data suggested that crocodile choline was a potent progression inhibitor of gastric cancer cells, which was correlated with mitochondrial apoptotic pathway and Notch pathway. Combining Notch1 inhibitors with crocodile choline might represent a novel approach for gastric cancer.